2021
DOI: 10.1002/crat.202000180
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Study of the Upgraded Hot Zone in Silicon Directional Solidification Process

Abstract: 2D global transient model for generation‐six (G6) GT‐style furnace and upgraded generation‐seven (G7) ALD‐style furnace in which all types of heat transfer and flow are included is established to investigate the thermal field, melt convection, melt–crystal (m–c) interface shape, thermal stress, growth rate, and Voronkov ratios in the growing silicon ingot. The modeling is verified by the heater power and temperature experiment. Simulation results show that the melt flow is relatively stronger as the furnace up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…In this paper, the twodimensional transient global models of G6 and G7 DS furnaces considering thermal convection, thermal radiation, melt and argon ow, phase transition, and impurities coupled transport were established. The differences between the G6 and G7 DS furnaces and the veri cations of the models can refer to in our published papers [10,12,21,23,24]. As shown in Fig.…”
Section: Geometry and Heat Transfer Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…In this paper, the twodimensional transient global models of G6 and G7 DS furnaces considering thermal convection, thermal radiation, melt and argon ow, phase transition, and impurities coupled transport were established. The differences between the G6 and G7 DS furnaces and the veri cations of the models can refer to in our published papers [10,12,21,23,24]. As shown in Fig.…”
Section: Geometry and Heat Transfer Modelmentioning
confidence: 99%
“…Wu et al [20] compared the thermal eld of G5 and G6 DS furnaces; the results showed that the crystal growth e ciency in the G6 furnace increased by 53.8%, and the average yield rate of the silicon ingots increased by 9%. Su et al [21] showed that the melt ow is relatively stronger as the furnace upgrades, and the temperature and gradient thermal stress in silicon ingot all increase. Nguyen et al [22] investigated the evolution of the thermal eld and ow eld during the crystal growth of GT-DSS G6 and G8 furnaces, and found differences in the structure of the melt ow.…”
Section: Introductionmentioning
confidence: 99%
“…The structured/unstructured hybrid grids are used to divide the computing region. Other detailed descriptions of the furnace modeling and the governing equations of heat transfer and fluid flow are included in our previous published work [23,24]. Figure 2 shows the AGDS used in our study, which is composed of an inner tube and outer tube.…”
Section: Model Description 21 Geometry and Heat Transfer Modelmentioning
confidence: 99%
“…The detailed description of heat and mass transfer models and the governing equations of heat transfer, ow, and melt convection used in the model, the boundary conditions and detailed transport equations of transportation of O and C impurities, material property parameters, and its simpli cations can be found in our previous studies [34][35][36] .…”
Section: Introductionmentioning
confidence: 99%